Role of contact allergens in chronicity and relapses of nummular eczema - Rattan, Renu; Tegta, Gita R.; Shanker, Vinay; Verma, Ghanshyam K.; Sharma, Anuj; Chauhan, Meena; Sharma, Abhishek (International Journal of Research in Dermatology, 2017)
Background: Endogenous eczemas are often complicated by exogenous factors like environment and contact allergens. Nummular eczema, a variant of endogenous eczema is no exception to this. Our study aimed at investigating the incidence of allergic contact dermatitis and finding offending agent responsible for chronicity or relapsing course of nummular eczema in patients from a hilly region with cold and dry environmental conditions. Methods: Forty patients of nummular eczema with a mean age of 39.1±19 years were patch tested with the Indian Standard Patch Test Series. Positive reactions were graded as per recommendations of International contact dermatitis research group. Results: Twenty one out of forty patch tested patients showed positive reactions. The most common allergens were found to be: fragrance mix in seven (17.5%) patients, nickel in five (12.5%) patients, PPD in three (7.5%) patients and gentamicin in two (5%) patients. Sensitivity to thiuram mix, black rubber mix, P. tert. butylphenol formaldehyde, neomycin, benzocaine and chinoform was observed in one patient each (2.5% each). Conclusions: Patients of nummular eczema of a hilly region are at a significant risk of developing allergic contact dermatitis owing to xerosis due to dry environmental conditions. This results in chronic nature of their disease. Patch testing should be considered in such patients and avoidance of offending allergens can improve their quality of life.